2009
DOI: 10.2527/jas.2008-1456
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in positional candidate genes on BTA14 and BTA26 affect carcass quality in beef cattle

Abstract: Several studies have reported the presence of carcass quality QTL on BTA14 and BTA26, with no specific genes being conclusively linked as their cause. The aim of this study was to identify polymorphisms in genes known to affect lipid metabolism in other species and to assess their association with carcass quality traits. Two genes located on BTA14, 2,4 dienoyl CoA reductase 1 (DECR1) and core binding factor, runt domain, alpha subunit 2, translocated to 1 gene (CBFA2T1), have been previously evaluated in other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…SNPs in genes that had previously been associated with intramuscular fat in some way, whether as MS, PSF, or IMF, were tested to see whether any were significantly ( P <0.05) associated to IMF in the GWAS study. Previous studies had found associations between MS, PSF, or IMF, and SNPs in the alphabetically listed candidate and positional candidate genes adiponectin, C1Q and collagen domain containing ( ADIPOQ ) [83], calpain 1 ( CAPN1 ) [84], carboxypeptidase E ( CPE ) [56], [85], CCAAT/enhancer binding protein (C/EBP) alpha ( CEBPA ) [86], the region containing the chemokine (C-X-C) motif receptor 4 ( CXCR4 ) gene near to the genes R3H domain containing 1 ( R3HDM1 ) and zinc finger, RAN domain containing 3 ( ZRANB3 ) [65], 2,4 dienoyl CoA reductase 1 ( DECR1 ) [87], fatty acid binding protein 4 ( FABP4 ) [88], fatty acid synthase ( FASN ) [59], fibroblast growth factor 8 ( FGF8 ) [87], growth hormone 1 ( GH1 ) [89], [90], growth hormone receptor ( GHR ) [91], insulin growth factor 2 ( IGF2 ) [92], leptin ( LEP ) [93], retinoic acid receptor-related orphan receptor C ( RORC ) [94], sterol regulatory element binding transcription factor 1 ( SREBF1 ) [95], steroyl-CoA desaturase ( SCD ) [96], thyroglobulin ( TG ) [97], and titin-cap (telethonin) ( TCAP ) [98]. For the trait LLPF, SNPs in the candidate genes CAST , CAPN1 and calpain 3 ( CAPN3 ) have been reported in cattle [46], [47], [48], [49], [50].…”
Section: Methodsmentioning
confidence: 99%
“…SNPs in genes that had previously been associated with intramuscular fat in some way, whether as MS, PSF, or IMF, were tested to see whether any were significantly ( P <0.05) associated to IMF in the GWAS study. Previous studies had found associations between MS, PSF, or IMF, and SNPs in the alphabetically listed candidate and positional candidate genes adiponectin, C1Q and collagen domain containing ( ADIPOQ ) [83], calpain 1 ( CAPN1 ) [84], carboxypeptidase E ( CPE ) [56], [85], CCAAT/enhancer binding protein (C/EBP) alpha ( CEBPA ) [86], the region containing the chemokine (C-X-C) motif receptor 4 ( CXCR4 ) gene near to the genes R3H domain containing 1 ( R3HDM1 ) and zinc finger, RAN domain containing 3 ( ZRANB3 ) [65], 2,4 dienoyl CoA reductase 1 ( DECR1 ) [87], fatty acid binding protein 4 ( FABP4 ) [88], fatty acid synthase ( FASN ) [59], fibroblast growth factor 8 ( FGF8 ) [87], growth hormone 1 ( GH1 ) [89], [90], growth hormone receptor ( GHR ) [91], insulin growth factor 2 ( IGF2 ) [92], leptin ( LEP ) [93], retinoic acid receptor-related orphan receptor C ( RORC ) [94], sterol regulatory element binding transcription factor 1 ( SREBF1 ) [95], steroyl-CoA desaturase ( SCD ) [96], thyroglobulin ( TG ) [97], and titin-cap (telethonin) ( TCAP ) [98]. For the trait LLPF, SNPs in the candidate genes CAST , CAPN1 and calpain 3 ( CAPN3 ) have been reported in cattle [46], [47], [48], [49], [50].…”
Section: Methodsmentioning
confidence: 99%
“…When coupled with economic analysis, the improvement in these traits can be weighed against potential deleterious effects in other traits. Numerous previous studies have identified SNP associated with economically important beef carcass characteristics (Kononoff et al, 2005;Nkrumah et al, 2005Nkrumah et al, , 2007Marques et al, 2009). Such knowledge has led to the commercialization of genetic testing technologies.…”
Section: Introductionmentioning
confidence: 98%
“…Core binding factor, runt domain, alpha subunit 2, translocated to 1 (CBFA2T1) is a protein that is encoded by the RUNX1T1 gene and is known to affect lipid metabolism in other species 54. Its polymorphism was found to have significant association with ultrasound marbling score in beef cattle 55. Calcium/calmodulin-dependent protein kinase II alpha (CAMK2A) contributes to myogenesis 56 and can be a candidate gene for activity-dependent skeletal muscle adaptation 57.…”
Section: Resultsmentioning
confidence: 99%